2021
DOI: 10.1111/mec.16055
|View full text |Cite
|
Sign up to set email alerts
|

Local climate adaptation and gene flow in the native range of two co‐occurring fruit moths with contrasting invasiveness

Abstract: Invasive species pose increasing threats to global biodiversity and ecosystems. While previous studies have characterized successful invaders based on ecological traits, characteristics related to evolutionary processes have rarely been investigated. Here we compared gene flow and local adaptation using demographic analyses and outlier tests in two co‐occurring moth pests across their common native range of China, one of which (the peach fruit moth, Carposina sasakii) has maintained its native distribution, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 104 publications
(174 reference statements)
2
21
0
Order By: Relevance
“…This is consistent with variation in the effective size of the three populations after the LGM (Fig. 4a ), and is also in agreement with the previous research 12 , 32 , 36 .…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with variation in the effective size of the three populations after the LGM (Fig. 4a ), and is also in agreement with the previous research 12 , 32 , 36 .…”
Section: Resultssupporting
confidence: 93%
“…Larvae of the oriental fruit moth bore for long periods into fruit and tree shoots; they often disperse via the transport of fruit or nursery stock. During the last century, the oriental fruit moth has spread to almost every continent (reaching a cosmopolitan distribution) and shows high invasiveness 36 . Population genetic analyses showed that the globally dispersed populations are likely from other recently colonized populations rather than from the refugial area of Sichuan 12 , 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid local adaptation of invasive alien species usually includes two aspects: phenotypic plasticity and genetic evolution ( Wellband and Heath, 2017 ; VanWallendael et al, 2018 ; Cao et al, 2021 ). Early studies on rapid adaptive evolution were mostly based on phenotypic changes between generations through common garden experiments or reciprocal transplant experiments ( Turner et al, 2014 ; Ochocki and Miller, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study investigated the population genetic structure of SAA in China using complete genome sequences. Population genetic structure of species can be inferred from mitochondrial genes and nuclear markers (Zhang et al, 2017;Cao et al, 2021). However, the complete mitogenome may accumulate more variations and provide valuable information for population genetic structure inference (Du et al, 2019(Du et al, , 2021.…”
Section: Discussionmentioning
confidence: 99%